Investors' Perceptions of Activism via Voting: Evidence from Contentious Shareholder Meetings* - Brochet, Francois; Ferri, Fabrizio; Miller, Gregory S. (Contemporary Accounting Research, 2021)
ABSTRACT Motivated by the increasing influence of shareholder votes on corporate policies, we examine investors' perceptions of activism via voting. To identify instances of activism via voting, we focus on annual meetings with at least one ballot item where a substantial fraction of shareholders is expected to vote against management's voting recommendation, indicating an increase in their monitoring activity. We define such meetings as “contentious.” Using a sample of almost 28,000 meetings between 2003 and 2012, we examine stock returns over the period between the proxy filing and the annual meeting. This period captures when investors learn about the contentious nature of the upcoming meeting and form expectations about its likely impact on firms' policies. We find that abnormal stock returns prior to contentious meetings are significantly positive and higher than those prior to noncontentious meetings. These higher abnormal returns increase with the contentiousness of the meeting; are more pronounced in firms with poor past performance, which are more likely to respond to shareholder pressure; and persist after controlling for firm‐specific news and proxies for risk factors. Our results are consistent with investors' expecting activism via voting to have a positive impact on firm value, on average, and cast doubts on regulatory attempts to restrict the use of shareholder votes.